Functional validation of ZbFAD2 and ZbFAD3 in the alkylamide biosynthesis pathway from Zanthoxylum bungeanum Maxim - Zhang, Jie; Wu, Zhaochen; Han, Nuan; Wang, Dongmei (Frontiers in Plant Science, 2022)
The spicy taste and medicinal properties of Zanthoxylum bungeanum are imparted by several alkylamides. Although most studies have focused on their isolation and identification, few have reported their biosynthesis pathways. In Z. bungeanum, among the multiple differentially expressed genes (DEGs) reported in the numerous varieties, some might contribute to alkylamide biosynthesis. However, they are not yet functionally validated. The current study explores the function of two genes, ZbFAD2 and ZbFAD3, in the alkylamide biosynthesis pathway. We analyzed their stable and transient expression in Arabidopsis thaliana and Nicotiana benthamiana, respectively. As compared with the wild-type (WT), the fatty acid content analysis indicated that ZbFAD2-A. thaliana transgenic seeds contained lower oleic acid and higher linoleic acid contents, while the ZbFAD3-A. thaliana transgenic seeds showed lower linoleic acid and higher α-linolenic acid levels. Moreover, hydroxy-α-sanshool, a major alkylamide, was considerably higher in the ZbFAD2-N. benthamiana transgenic plants (0.2167 ± 0.0026 mg/g) than in the WT (0.0875 ± 0.0049 mg/g), while it was lower in the ZbFAD3-N. benthamiana transgenic plants (0.0535 ± 0.0037 mg/g). These results suggest that both ZbFAD2 and ZbFAD3 are vital alkylamide biosynthesis enzymes in Z. bungeanum. Our study should not only help scale-up the alkylamide production, but also establish the role of the uncharacterized genes.